Letter: the diagnostic and prognostic significance of liver histology in alcoholic hepatitis. Issue 6 (23rd August 2021) - Vaz, Karl; McLean, Catriona; Majeed, Ammar; Little, Robert; Kemp, William; Roberts, Stuart
LINKED CONTENT: This article is linked to Forrest et al and Forrest & Goldin papers. To view these articles, visit https://doi.org/10.1111/apt.16157 and https://doi.org/10.1111/apt.16559